Diffusion-activated high performance ZnSnO/Yb2O3 thin film transistors and application in low-voltage-operated logic circuits. (20th April 2021) - Yang, Bing; He, Gang; Wang, Wenhao; Zhang, Yongchun; Zhang, Chong; Xia, Yufeng; Xu, Xiaofen
Abstract: The flourishing metal-oxide high- k dielectric materials have been regarded as the vital components of low voltage operated flexible transparent electronic devices. We herein report that ytterbium oxide (Yb2 O3 ) and ZnSnO (ZTO) thin films were firstly integrated into ZTO-based thin film transistors (TFTs) with superior performance. Results have indicated that the 500 ℃-annealed ZTO/Yb2 O3 TFTs possess the large saturation mobility of 9.1 cm 2 V −1 S −1 and the high on/off current ratio of 2.15 × 10 7, which even surpass those of reported In-based TFTs. The deteriorative electrical properties in the aging process can be attributed to the carrier capture mechanism. However, the 460 ℃-processed TFTs demonstrate a tenfold increase in saturated mobility and an increase in on/off current ratio after 10 days aging. The inspiring electrical properties are attributed to the diffusion-activated carrier enhancement mechanism and electrons donor role of water molecular, which introduces a facile method to boost the device performance at lower processing temperatures. The neglected threshold voltage variations of 0.06 V and −0.2 V have been detected after bias stability experiments. The superior bias stability can be attributed to the charge delay effect induced by the continuous electric field. Meanwhile, the ultrahigh on/off current ratio of 1.1 × 10 7 and the recoverable transferring performance have verified the aging-activated mechanism. To confirm its potential application in digital circuits, a resistor-loaded inverter with gain of 5.6 has been constructed and good dynamic response behavior have been detected at a low voltage of 2 V. As a result, it can be concluded that the high temperature annealing TFTs need immediate encapsulation, while the performance of the lower temperature processing samples can be optimized after aging treatment, indicating the potential prospect in low power consumption large-scale flexible transparent devices.